Application of Hardware and Software Complex for Individualisation of Students' Sport and Recreational Physical Activities - O. N. Moskovchenko; L. V. Zakharova; N. V. Tretyakova; N. V. Lyulina; O. A. Kattsin; G. S. Savolaynen (Russian State Vocational Pedagogical University, 2019)
Introduction. Considerably increased intensity of educational process in higher education institution frequently becomes the reason of deterioration in students' health. The traditional system of physical education (PE), designed to maintain good health of students in new conditions, does not cope with an objective defined. Obviously, health preservation of a person is promoted by physical activities, which are adequate to his or her psycho-physiological characteristics and should be worked out individually for each person. The estimations can be carried out in different ways and on the basis of different parameters, among which the authors emphasise heart rate variability and vegetative regulation that act as indicators of adaptation and adaptive activity of an organism.The aim of the present research was to identify individual appropriate physical load for students with various motion behaviour types through the use of informational technologies (IT).Methodology and research methods. The research was based on health-preserving and differentiated approaches to physical education organisation. Health preservation was the leading principle of the approaches taken into account. The empiric research methods included content analysis, comparative analysis, synthesis and generalisation. The survey sampling and processing of experimental data were carried out by means of the hardware and software complex (HSC).Results and scientific novelty. The authors studied and documented the interconnection of students' heart rate variability, taking into account their age and sex peculiarities, motion behaviour and medical groups. The regulatory systems tension degree differentiation was offered and approved. The criteria to determine a vegetative tonus of students (eutony, vagotony, sympathicotony) were identified on the basis of nonparametric algorithms of automatic classification, recognition of samples and theorem of statistical hypothesis tests. Thus, PE teacher can systematically increase the adaptation potential of students due to inclusion in a training course of corrective and rehabilitation programmes. The efficiency of IT in sport and recreational physical activities was scientifically based. The diagnostics on the basis of HSC, which includes data filtering, determination of parameters of selection of the histogram, graphic display of results of the spectrogram, allows specialists: to estimate the work of cardiovascular system and adaptatively compensation abilities of vegetative regulation mechanisms in a comprehensive, accurate and rapid way; to determine various violations of heart rhythm at donosological level (sick sinus node, atrial fibrillation, etc.); to select options for individual physical and training loads.Practical significance. The authors' scientific and methodological approach to the organisation of sport activities raises the subject of PE in higher educational institutions to a significantly upgraded level: through computer technologies, it becomes the effective instrument of health-preserving activity, which is the promising direction in PE of student's youth. The research results can be used in practice of educational institutions of various types.